Molecular identification of commercially important species of Nemipterus (Perciformes: Nemipteridae) in surrounding seas of Malaysia - AYESHA IMTIAZ; DUONG THUY YEN; SITI AZIZAH MOHD NOR; DARLINA MD NAIM (Biodiversitas Journal of Biological Diversity, 2016)
Imtiaz A, Duong TY, Nor SAM, Naim DM. 2016. Molecular identification of commercially important species of Nemipterus (Perciformes: Nemipteridae) in surrounding seas of Malaysia. Biodiversitas 17: 571-577. The genus Nemipterus is a group of coral fishes which are morphologically diversified in coloration and distribution pattern. In this study, the mitochondrial Cytochrome coxidase-I (COI) gene was analyzed for genetic identification of 127 samples of genus Nemipterus from Malaysia waters. Sequence analysis of COI based data clearly distributed ten putative species into four distinct clusters clades. Intra-specific genetic distance values of 2.7%, 3.4% were observed in N. japonicus and N. nemurus which require more detailed analysis of the taxonomic status of some of the individuals attributing to slightly atypical values. Neighbor joining (NJ) tree shows a low genetic structuring in N. japonicus. Populations from Indian Ocean and South China Sea are isolated from each other but both share genetic structure with the population from the Straits of Malacca, suggesting the possibility of the latter acting as a barrier to the movement of this species between the two neighboring seas.